Generative AI Meets Cataloging Practice: Findings from a Comparative Pilot Study. - Heng, Greta; Lampron, Patricia; Han, Myung-Ja (Information Technology & Libraries, 2026)
This study evaluates the performance of four generative AI models--ChatGPT, DeepSeek, Gemini, and Copilot--in generating descriptive metadata for bibliographic resources. Models were tested on a small, diverse set of resources using four prompt types: a basic prompt, a basic prompt with an example, a detailed prompt referencing Resource Description and Access (RDA) guidelines, and a detailed prompt with an example. Results show that both detailed RDA guidance and the inclusion of sample outputs improved metadata quality, particularly in formatting and field structure. While DeepSeek and ChatGPT showed better performance on the tasks, all models displayed limitations in parsing and following the prompts, using descriptive metadata fields, analyzing subject headings, and assigning URIs. These findings suggest that while generative AI holds potential to assist in metadata creation, its current capabilities fall short of meeting cataloging standards without human review.